Determinants of pegivirus persistence, cross-species infection, and adaptation in the laboratory mouse. - Kylie Nennig; Satyapramod Murthy; Sara Maloney; Teressa M Shaw; Mark Sharobim; Eduard Matkovic; Simi Fadiran; Malorie Larsen; Mitchell D Ramuta; Arthur S Kim; John R Teijaro; Joe Grove; et al. (PLoS Pathogens, 2024)
Viruses capable of causing persistent infection have developed sophisticated mechanisms for evading host immunity, and understanding these processes can reveal novel features of the host immune system. One such virus, human pegivirus (HPgV), infects ~15% of the global human population, but little is known about its biology beyond the fact that it does not cause overt disease. We passaged a pegivirus isolate of feral brown rats (RPgV) in immunodeficient laboratory mice to develop a mouse-adapted virus (maPgV) that established persistent high-titer infection in a majority of wild-type laboratory mice. maRPgV viremia was detected in the blood of mice for >300 days without apparent disease, closely recapitulating the hallmarks of HPgV infection in humans. We found a pro-viral role for type-I interferon in chronic infection; a lack of PD-1-mediated tolerance to PgV infection; and multiple mechanisms by which PgV immunity can be achieved by an immunocompetent host. These data indicate that the PgV immune evasion strategy has aspects that are both common and unique among persistent viral infections. The creation of maPgV represents the first PgV infection model in wild-type mice, thus opening the entire toolkit of the mouse host to enable further investigation of this persistent RNA virus infections.